A morpholigical and molecular phylogenetic analysis of Malaysian kerivoula (Chiroptera : Vespertilionidae) - Noor Haliza, Hassan (Universiti Malaysia Sarawak, (UNIMAS), 2009)
Morphometric and phylogenetic analyses were done on six species of Kerivoula from Malaysia. Morphological studies could only be done on five out of the six kerivoula species available for this research, namely K. papillosa, K. Lenis, K. pellucid, K. hardwickii and K. minuta. Thirty-one characters of the external body, skull and dentition were taken from 47 adult individuals of Kerivoula. Three separate analyses were done on the morphological data; (1) clustering analysis, (2) principal component analysis (PCA) and (3) discriminant function analysis (DFA) were applied to the data. The findings from all the three analyses supported the groupings of the Kerivoula samples into six different groups; namely, K. minuta, K. hardwickii, K. pellucid, K. lenis and K. papillosa. The findings of this study were expected to aid in the taxonomy and future management and conservation plans for this genus